COMMUNITY SATISFACTION RESEARCH ON PUBLIC SERVICES IN BARRU DISTRICT, SOUTH SULAWESI - Wahyul AZ (Meraja journal, 2021)
This study aims to determine the level of community satisfaction with public services studied at 3 SKPD offices in Barru district from the aspect of (a) service procedures getting a score of 2.87, (b) service requirements getting a score of 2.86, (c) clarity of service officers getting a score of 2.84. This study uses an approach This research was conducted by applying a survey method with a quantitative descriptive form. The survey method is used to help researchers to obtain an overview or general trend regarding public attitudes or opinions towards public services. This is indicated by the number of respondents who complain about the lack of clarity of the flow and service procedures carried out by the service office and the service time which is felt to be very slow by the community. There are still many people who still use the services of “insiders” in the process of managing their letters, which is also evidence that the public service process has not been running well enough in the Barru district.